Update: The Ideology of Creativity - Hanson, Michael Hanchett (Farol, 2024)
Ten years ago, I wrote Worldmaking: Psychology and the Ideology of Creativity, tracing the ideological functions of the concept of creativity over time. The world and the psychology of creativity have changed. From developmental, sociocultural, and complex systems perspectives, how can we understand and respond to the turbulences that are emerging in the political, environmental, and technological landscapes, along with destabilizing social fragmentation and heightened geopolitical conflict?